A REVIEW ON- RECENT ADVANCEMENT IN THE DEVELOPMENT OF RAPID DISINTEGRATING TABLET: Pharmaceutical Science-Pharmaceutics - ASHISH, PATIDAR; P, MISHRA; P, MAIN; M.S., HARSOLIYA; S, AGRAWAL (International Journal of Life Science and Pharma Research, 2011)
Recent advances in novel drug delivery (NDDS) aims to enhance safety and efficacy of drug molecule by formulating a convenient dosage form for ease of administration and to achieve better patient compliance. In the recent trend one such approach the development of rapid disintegrating tablets formulation is emerging and gaining popularity because it is easy to administer and leads to better patient compliance. These dosage forms are placed in the mouth, allowed to disperse or dissolve in the saliva. They release the drug as soon as they come in contact with the saliva, thus obviating the need for water during administration. The aim of this article is to review the progress of the evolving technologies and super disintegrating agents in the formulation, manufacturing and evaluation of these tablets. This article also discusses the new evaluation methodologies for these rapid disintegrating tablets. Various modifications in the conventional evaluation and use of specialized instruments are found to be essential in the testing of these dosage forms. In the present review the formulation techniques and different technologies are discussed.